The EU-Directive on the Legal Protection of Databases and the Incentives to Update: An Economic Analysis - Christian Koboldt (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1996)
The database directive, initiated by the European Commission in 1992 and due to be finalised in the near future, establishes a two-tiered system of protection, amending copyright with a sui generis rule that grants protection against unfair extraction. The terms of protection are extended if the producter makes "substantial changes" to update the database. This paper analyses the incentive to update created by the database directive. In contrast to the usual findings of the literature on the incentive effects of intellectual property rights, we find that, although in most cases the incentives to update a database are insufficient from society's point of view, the possibility of extending the term of protection by making 'substantial changes' in the database may create an incentive for excessive updating. This leads to conclusions about what should be considered a substantial change – – Die in Datenbank-Direktive, deren endgültige Fassung in Kürze vorliegen wird, garantiert Datanbankproduzenten einen zweistufigen Schutz: Neben dem Urheberrecht existier ein sui generis Recht das vor unlauteren Auszügen schützt und dessen Schutzdauer sich verlängert, wenn der Produzent die Datenbank durch substantielle Änderungen aktualisiert. Dieses Papier befaßt sich mit den Anreizen zur Aktualisierung. Im Gegensatz zu den üblichen Anreizwirkungen von Rechten zum Schutz geistigen Eigentums ergibt sich hier ein Anreiz zu exzessiven Investitionen in die Aktualisierung von Datenbanken. Produzenten nehmen Aktualisierungen auch dann vor, wenn dies gesamtgesellschaftlich nicht wünschenswert ist. Aus dieser Erkenntnis ergeben sich Folgerungen für die Festlegung dessen, was als substantielle Änderung gelten sollte.
Keywords: K11; K19; 330; Copyright; databases; updating; Datenbank; Urheberrecht; Ökonomischer Anreiz; Theorie; EU-Staaten